A~God Gap Driving a~Revolution from Conservative to the Far Right in the United States—With Significance for Europe? - Gert Pickel; Susanne Pickel (Politische Vierteljahresschrift, 2023)
For some time now, the Christian right in the United States has sought proximity to the Republican Party. However, it is only since Donald Trump's presidency that the central desires of the Christian right for a moral change have been fulfilled. This hope has existed since the 1980s and has been expressed in far-above-average voting behavior, especially of white evangelicals and Pentecostals for the Republicans. Thus, the Republicans' focus on moral issues increasingly links them to the image of white Christian nationalism. This stance opposes transgender issues, homosexuality, abortion, and critical race theory and is preoccupied with America's founding era and racist structures. Favored by the bipolar electoral system and driven by a~politics that differentiates between good and evil, a~political polarization is establishing itself that leaves hardly any room for compromise. These developments are not limited to the United States but are beginning to migrate globally, as recent incidents in Brazil, Serbia, and Russia show. The United States can be seen as a~prototypical case of a~particular form of transformation of a~democracy into a~polarized political system. A~certain understanding of religion plays just as much a~role in this as the rejection of plurality, especially at the level of sexual and gender diversity. – – Die Christliche Rechte in den USA sucht schon seit längerer Zeit die Nähe zur den Republikanern. Doch erst seit der Präsidentschaft von Donald Trump haben sich die zentralen Wünsche der Christlichen Rechten in den USA nach einem moralischen Wandel erfüllt. Diese Hoffnung besteht seit den 1980er-Jahren und drückt sich in einem überdurchschnittlichen Wahlverhalten der Republikaner durch weiße Evangelikale und Mitglieder der Pfingstkirchen aus. Die Fokussierung der Republikaner auf moralische Fragen verbindet sie zunehmend mit dem weißen christlichen Nationalismus. Dieser wendet sich gegen Transgender, Homosexualität, Abtreibung und eine Beschäftigung mit der Gründungszeit Amerikas und rassistischen Strukturen, wie es die Critical Race Theory tut. Begünstigt durch das bipolare Wahlsystem und angetrieben von einer Politik, die zwischen Gut und Böse unterscheidet, etabliert sich eine politische Polarisierung, die kaum noch Raum für Kompromisse lässt. Diese Entwicklungen sind nicht auf die USA beschränkt, sondern beginnen, weltweit zu wandern, wie die jüngsten Vorfälle in Brasilien, Serbien oder Russland zeigen. Die Vereinigten Staaten können als prototypischer Fall für eine besondere Form der Umwandlung einer Demokratie in ein polarisiertes politisches System angesehen werden. Ein bestimmtes Religionsverständnis spielt dabei ebenso eine Rolle wie die Ablehnung von Pluralität~– insbesondere auf der Ebene der sexuellen und geschlechtlichen Vielfalt.
Keywords: 320; Religion; Conservativism; Polarization; Far right; White Christian nationalism; Konservativismus; Polarisierung; Extreme Rechte; Weißer christlicher Nationalismus